Presence of human papillomavirus infection determined by hybrid capture assay in cervical lesions in a Venezuelan population. - Correnti, Maria; Cavazza, María Eugenia; Herrera, Odalis; Rodríguez, Armando (Investigación Clínica, 2013)
Â  The aim of this study was to establish the presence of HPV infection in cervical lesions in a Venezuelan population, by Hybrid Capture As say II (HCA II), and its association with cytological diagnosis. The study included 1483 cervical samples analysed at Laboratorios CITOMED, Caracas, Venezuela, from 2005 to 2007. The woman age range was between 20 and 58 years, and the mean age was 28.8. HPV infection was determined using HCA II. The cytological diagnosis of the smears showed LSIL in 1120/1483 samples (75.5%), HSIL in 354/1483 (23.9%) and ASC-US, in 9/1483 (0.6%). The positivity of HPV DNA detected by HCA II was 54.6% (811/1483). Of the positives cases, 138/811 (17%) presented HPV DNA of low oncogenic risk and 673/811 (82.9%) had high-risk HPV. There were significant differences in the low and high oncogenic HPV type frequencies of the evaluated samples (p > 0.0001). Low risk HPV types were detected in 127 cases of LSIL, 9 of HSIL and 2 of ASC-US. High-risk HPV was detected in most of the cases: 361 LSIL, 308 HSIL and 4 ASC-US. Our study showed a high presence of cervical infection by human papillomavirus of a high risk genotype. Our results contribute to the epidemiological data that report diversity in the prevalence rates in different countries.